The Substantial Balance of Internal Energy (IE) for Extensive Quantities as Viewed by the Balance Theory - Wrzesiński, Z. (Engineering Transactions, 2002)
The article presents the balance axiom and the basic balance leading to the referential balances of a scalar and vector extensive quantity (EQ). Next the substantial balance of internal energy (IE) has been done, defining the production part which is the sum of IE creation and annihilation, as well as the exchange part which is the sum of IE inflow and outflow through the boundaries of a substantial system. The substantial balance of internal energy (IE) achieved in this way has been reduced to the balance under the conditions of a reversible change, to obtain finally the balance of IE, commonly referred to as the first principle of thermodynamics for extensive quantities (EQs).